2005
DOI: 10.1677/erc.1.01029
|View full text |Cite
|
Sign up to set email alerts
|

Management of patients with adrenal cancer: recommendations of an international consensus conference

Abstract: Adrenocortical carcinomas are rare, highly malignant tumors that account for only 0.2% of deaths due to cancer. Given the limited number of patients seen in most medical centers with this diagnosis, series usually reported are small and clinical trials not randomized or blinded. In an attempt to answer important questions concerning the management of patients with adrenal cancer, a consensus conference was organized and held at the University of Michigan in Ann Arbor, MI, 11–13 September 2003, with the partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
281
0
34

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 383 publications
(319 citation statements)
references
References 63 publications
(64 reference statements)
4
281
0
34
Order By: Relevance
“…During the International Consensus Conference on adrenocortical carcinoma in 2003, 15 the first randomized phase 3 trial of treatment for this rare tumor was planned. In this trial, called the First International Randomized Trial in Locally Advanced and Metastatic Adrenocortical Carcinoma Treatment (FIRM-ACT), we compared the two most successful regimens in patients with advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…During the International Consensus Conference on adrenocortical carcinoma in 2003, 15 the first randomized phase 3 trial of treatment for this rare tumor was planned. In this trial, called the First International Randomized Trial in Locally Advanced and Metastatic Adrenocortical Carcinoma Treatment (FIRM-ACT), we compared the two most successful regimens in patients with advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical analysis with Ki67/MIB1 has been widely performed in various human malignancies, and its role both as a diagnostic tool and as a prognostic factor has been well established [10,11]. In human ACC, a high mitotic rate has been reported to be a significant and independent marker of poor clinical courses [18], and Ki67/MIB1LI was significantly related to mitotic count [12] and other parameters of cell proliferation such as expression of DNA topoisomerase type IIa [14] and p27 [16]. Previous studies including ours reported that the cut-off values of Ki67/MIB1LI between 2.5% and 5.0% reliably differentiated ACC from adrenal adenomas [8,[12][13][14][15][16][17]20].…”
Section: Discussionmentioning
confidence: 99%
“…Complete follow-up data were available for all patients. The following data were collected for each patient: demographics, localization and size of tumors evaluated by CT and/or MRI, tumor staging at initial presentation assessed by the Sullivan modification of the McFarlane system with TNM definitions [1,18,19], hormonal data at initial presentation, disease status at the end of followup, date of last follow-up, date and cause of death, and additional therapies including administration of mitotane. The resection of the primary tumor was considered to be curative in all cases except for one case (corresponding to case 1 in Table 1), which exhibited a metastatic lesion at lung at the time of the first surgery.…”
Section: Patients Tissue Specimens and Follow-upmentioning
confidence: 99%
“…The adjuvant use of mitotane (o,p 0 -DDD), an adrenolytic drug used for treating advanced ACC since the 1960s (3,4,8), has become increasingly popular after the demonstration that post-operative mitotane treatment was associated with a significantly reduced risk of recurrence and death in a large series of patients with radically operated ACC (9,10). Given its retrospective nature, however, this study could not provide a definitive demonstration of the efficacy of mitotane in the adjuvant setting (11,12).…”
Section: Introductionmentioning
confidence: 95%
“…Surgery is the mainstay of therapy and complete surgical removal of ACC is the most important prognostic factor for longterm survival together with stage. Recurrence after apparently complete resection is frequent and may be found in up to 70-85% of patients with high proliferation index or locally advanced disease (3,4,5,6,7), an observation suggesting that adjuvant treatment concepts have a major role in ACC management.…”
Section: Introductionmentioning
confidence: 99%